2013
DOI: 10.1007/s11033-012-2433-y
|View full text |Cite
|
Sign up to set email alerts
|

Slow N-acetyltransferase 2 genotype contributes to anti-tuberculosis drug-induced hepatotoxicity: a meta-analysis

Abstract: Pathogenesis and genetic factors influencing predisposition to antituberculosis drug-induced hepatotoxicity (ATDH) are not clear. Polymorphism at the genetic locus of a drug and xenobiotic compound metabolizing enzyme, N-acetyltransferase type 2 (NAT2), is reported to be associated with the excess generation of toxic reactive metabolites. To date, many case-control studies have been carried out to investigate the relationship between the NAT2 polymorphisms and ATDH, but the results have been inconsistent. To i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
42
1
10

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 25 publications
5
42
1
10
Order By: Relevance
“…NAT2 polymorphisms were initially discovered as risk factor for drug-induced liver injury (DILI) in tuberculosis patients receiving isoniazid therapy (Hughes et al 1954). Studies on anti-tuberculosis drug-induced hepatotoxicity (ATDH) are mostly conducted in East Asian and South American populations where tuberculosis is a major health concern (Daly 2013;Du et al 2013). A recent meta-analysis indicated that ultra-slow acetylators are at highest risk of ATDH (Selinski et al 2014) though results have to be interpreted with care due to the absence of NAT2*5B in East Asians.…”
mentioning
confidence: 99%
“…NAT2 polymorphisms were initially discovered as risk factor for drug-induced liver injury (DILI) in tuberculosis patients receiving isoniazid therapy (Hughes et al 1954). Studies on anti-tuberculosis drug-induced hepatotoxicity (ATDH) are mostly conducted in East Asian and South American populations where tuberculosis is a major health concern (Daly 2013;Du et al 2013). A recent meta-analysis indicated that ultra-slow acetylators are at highest risk of ATDH (Selinski et al 2014) though results have to be interpreted with care due to the absence of NAT2*5B in East Asians.…”
mentioning
confidence: 99%
“…A meta-analysis study showed that the SA genotype of NAT2 was significantly associated with increased risk of antituberculosis drug hepatotoxicity in East Asians, South Asians, Brazilians and Middle Eastern when stratified by ethnicity. 12 Another meta-analysis study reported significant association between slow acetylator and prostate cancer in Asians. 13 Many studies showed that NAT2 slow acetylator alleles are associated with several disease risks.…”
Section: Discussionmentioning
confidence: 99%
“…http://mji.ui.ac.id A previous reported study revealed that NAT2*6A is an important genetic marker for the risk of hepatotoxicity due to anti-tuberculosis treatment in Chinese, Japanese, Korean 12 and Indonesian Javanese and Sundanese. 5 A meta-analysis of 26 case-control studies also reported that the NAT2 SA genotype was a risk factor of antituberculosis drug induced liver injury (AT-DILI), but the associations are diverse in different ethnic populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-genetic factors include female sex, race, and environmental factors such as alcohol intake (Pande et al, 1996;Lee et al, 2002;Marra et al, 2007;de Castro et al, 2010). The genetic factors are involved in drug metabolism, transport, and immune and antioxidant responses, and include N-acetyltransferase 2 (NAT2), BTB and CNC homology 1 (BACH1), tumor necrosis factor-a (TNF) and adenosine triphosphate binding cassette B1 (ABCB1) (Yimer et al, 2011;Kim et al, 2012;Nanashima et al, 2012;Du et al, 2013).…”
Section: Introductionmentioning
confidence: 99%